AC Voltage Control of DC/DC Converters Based on Modular Multilevel Converters in Multi-Terminal High-Voltage Direct Current Transmission Systems - Rui Li; John E. Fletcher (Energies, 2016)
The AC voltage control of a DC/DC converter based on the modular multilevel converter (MMC) is considered under normal operation and during a local DC fault. By actively setting the AC voltage according to the two DC voltages of the DC/DC converter, the modulation index can be near unity, and the DC voltage is effectively utilized to output higher AC voltage. This significantly decreases submodule (SM) capacitance and conduction losses of the DC/DC converter, yielding reduced capital cost, volume, and higher efficiency. Additionally, the AC voltage is limited in the controllable range of both the MMCs in the DC/DC converter; thus, over-modulation and uncontrolled currents are actively avoided. The AC voltage control of the DC/DC converter during local DC faults, i.e., standby operation, is also proposed, where only the MMC connected on the faulty cable is blocked, while the other MMC remains operational with zero AC voltage output. Thus, the capacitor voltages can be regulated at the rated value and the decrease of the SM capacitor voltages after the blocking of the DC/DC converter is avoided. Moreover, the fault can still be isolated as quickly as the conventional approach, where both MMCs are blocked and the DC/DC converter is not exposed to the risk of overcurrent. The proposed AC voltage control strategy is assessed in a three-terminal high-voltage direct current (HVDC) system incorporating a DC/DC converter, and the simulation results confirm its feasibility.